PEMBANGUNAN SISTEM PAKAR UNTUK DIAGNOSIS PENYAKIT TULANG DAN SENDI - Hafiz Budi Firmansyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2017)
Abstract—In Indonesia the numbers of orthopaedic surgeons are still not able to cover all demand. Badan Pusat Statistik (2015) reported that there are merely two orthopaedic surgeons in Lampung province having to serve about 8.117.268 people. Meanwhile, based on Ministry of Health of Republic of Indonesia, the ideal ratio between doctor and people is 12.2 doctor for each 100.000 people. Besides that, sometimes the surgeons need to serve more than one medical facility. Consequently, the patients might feel unpleasant. The lack of human resources becomes the main reason for developing expert system for diagnosing orthopaedic diseases. The expert system is able to diagnose orthopaedic diseases as well as fracture, dislocation, osteoarthritis and osteoporosis. The system is developed by using forward chaining methodology. This methodology is suitable for identifying a disease based on their symptoms. The result shows that the expert can answer 45 % of questions by identifying 6 main symptoms without continuing to following symptom questions.